LEARNING MANAGEMENT SYSTEMS: ENGINEERING THE EDUCATION INDUSTRY TO EDUCATE THE INDUSTRIAL ENGINEER - Van Dyk, L. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: A learning management system (LMS) is any infrastructure on which e-learning can be built and delivered. In this article two sides of the LMS coin are investigated: On the one side, it is argued that industrial and systems engineering skills are equally relevant for learning systems as for as for any other system. To support this argument, an analogy is drawn between the management of learning systems and the management of manufacturing systems. On the other side of the coin, the educational issues and concerns related to implementing an LMS at the University of Pretoria are investigated by means of a case study in the Industrial Engineering department. It is concluded that the industrial engineering educator is in the unique position of understanding and contributing towards the engineering of the education industry whilst educating the industrial engineer. AFRIKAANSE OPSOMMING: